The Effect of Oksitosin Induction Management on Preeclampsia to the Hyperbilirubinemia Incidence : Case Report - Adelbertha Berkanis; Ivon Wittiarika; Rize Amalia; Siti Haniah (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2025)
Around 3% of 120 million newborns experience neonatal jaundice Every year. It was estimated that the condition affects at least 481,000 babies and causes approximately 114,000 deaths globally. Case report: A 33-year-old woman P3A0 with pregnancy complications of preeclampsia gave birth to her 3rd child by oksitosin induction at 36/37 weeks gestational age. The mother has received continuity of midwife care since 22/23 weeks of pregnancy. On the 6th day after birth, the baby experienced Kramer IV neonatorum jaundice and it was then referred to the hospital. The results of total bilirubin examination at the hospital were 24 mg/dl. The parents received counseling by telehealth and home visits about on breast milk expressed, parent support, counseling parents regarding the nutritional and fluid adequacy of providing on-demand breast milk without formula milk mixture, personal hygiene, and thermoregulation. Conclusion: The management of pregnancy complications using oksitosin induction was considered to have an impact on neonatal outcomes, such as neonatal jaundice. So, it was recommended to do it carefully by considering the benefits compared to the risks. Because hyperbilirubinemia management aims to reduce morbidity, disability, and mortality.